"School is life, not a preparation for life"-John Dewey : democratic practices in middle grades education - Roney, Kathleen; Lipka, Richard P. (Emerald Publishing Limited : Information Age Publishing, Inc., 2021)
"Teacher-pupil planning means teachers and students working in a partnership to articulate a problem/concern, develop objectives, locate materials/resources, and evaluate progress. The intent of this volume of Middle Level Education and the Self-Enhancing School titled, "School is Life, Not a Preparation for Life"-John Dewey: Democratic Practices in Middle Grades Education, is to take the thoughts about the middle grades school curriculum presented in volume one (Middle Grades Curriculum: Voices and Visions of the Self-Enhancing School) and demonstrate the efforts taking place in teacher education programs and middle grades classrooms today. Volume two is organized into two parts, efforts within teacher education programs and efforts of practitioners in the middle grades classrooms. We asked authors in both contexts to address the following questions: 1. Antecedents: What knowledge, skills and dispositions must be in place in all stakeholders to have teacher-pupil planning serve a central role in the middle grades teacher education program or middle grades classroom? 2. Implementation: What does the teacher-pupil planning process look like within your teacher education program or middle grades classroom? 3. Outcomes: What benefits (knowledge, skills, and dispositions) are derived from the implementation of teacher-pupil planning in your teacher education program or your middle grades classroom?"-- Provided by publisher.
Keywords: Middle school education -- Curricula.; Teacher-student relationships.; Student participation in administration.; Teachers -- Training of.; Democracy and education.; Education -- Curricula.; Primary and middle schools.; Curriculum planning and development.; elektronické knihy; electronic books